One-Dimensional Assembly of Conductive and Capacitive Metal Oxide Electrodes for High-Performance Asymmetric Supercapacitors - Harilal, Midhun; Baiju, Vidyadharan; Izan Izwan, Misnon; Anilkumar, Gopinathan M.; Lowe, Adrian; Jamil, Ismail; M. M., Yusoff; Rajan, Jose (American Chemical Society, 2017)
A one-dimensional morphology comprising nanograins of two metal oxides, one with higher electrical conductivity (CuO) and the other with higher charge storability (Co3O4), is developed by electrospinning technique. The CuO–Co3O4 nanocomposite nanowires thus formed show high specific capacitance, high rate capability, and high cycling stability compared to their single-component nanowire counterparts when used as a supercapacitor electrode. Practical symmetric (SSCs) and asymmetric (ASCs) supercapacitors are fabricated using commercial activated carbon, CuO, Co3O4, and CuO–Co3O4 composite nanowires, and their properties are compared. A high energy density of ∼44 Wh kg–1 at a power density of 14 kW kg–1 is achieved in CuO–Co3O4 ASCs employing aqueous alkaline electrolytes, enabling them to store high energy at a faster rate. The current methodology of hybrid nanowires of various functional materials could be applied to extend the performance limit of diverse electrical and electrochemical devices.